Estimation of Environmental Efficiency for the Liquefied Gas Use as a Motor Fuel in the Internal Combustion Engine of Motor Vehicles - Simonyan, A. R. (ՀԱԱՀ հիմնադրամ)
Currently, the use of various types of alternative motor fuels, such as natural gas, methane (in liquefied or compressed form) and liquefied petroleum gas (LPG), has become more common in the world. In addition, various studies are carried out on the application of biological, synthetic fuels, dimethyl ether, etc. The widespread use of each of these fuels in internal combustion engines has both advantages and disadvantages, measured not only in terms of economic attractiveness, but also in terms of environmental safety. This article provides a method for estimating the environmental efficiency of liquefied gas as a motor fuel in vehicles.
Keywords: Agricultural Engineering